A confirmatory factor analysis of the Spiritual Transcendence Index: assessing spirituality in a sample of Latino college students. Issue 5 (27th May 2016) - MacMillan, Thalia; Luna, Naelys
ABSTRACT: Research has documented that spirituality is an essential component of health and mental health. Therefore, it is important to carefully examine the psychometric properties of instruments used to operationalise this construct. This study examined the validity and reliability of the Spiritual Transcendence Index (STI) among Latino college students. The sample involved 593 Latino college students who filled out a battery of questionnaires. Results supported the validity and reliability of the two factors of spirituality: spiritual beliefs and believing in God's presence. Additional research is needed to examine spirituality within Latino subgroups due to the heterogeneity of this population.